12) We first take care of the exponents: log_6 z + log_6 (x^2) - log_6 (y^3). Then we condense into a single expression: log_6 (zx^2 / y^3)
13) 5 + 8log_7 (v + 10) = 298log_7 (v + 10) = 24log_7 (v + 10) = 37^3 = v + 10343 = v + 10v = 333
14) log_5 (x^2) + log_5 (4) = 1log_5 (4x^2) = 15^1 = 4x^25/4 = x^2x = +/- sqrt(5) / 2 = +/-1.1180
*No extraneous solutions here, since the equation only uses x^2, not x.
15) -6*12^(b+7) +1 = -6-6*12^(b+7) = -712^(b+7) = 7/6
log 12^(b+7) = log(7/6)(b+7) log 12 = log (7/6)b+7 = log(7/6) / log(12) = 0.06203b = -6.9380